Omega-3 Fatty Acid Supplementation and Its Impact on Systemic Inflammation and Body Weight in Patients With Cancer Cachexia—A Systematic Review and Meta-Analysis - de Castro, Gabriela Salim; Andrade, Márcia Fábia; Pinto, Flaydson Clayton Silva; Faiad, Jaline Zandonato; Seelaender, Marília (Frontiers in Nutrition, 2022)
Body weight loss and inflammation are major alterations related to cancer cachexia, an important wasting syndrome highly prevalent in many types of cancer. Nutritional components modulate inflammation in several chronic diseases. Omega-3 fatty acids (n-3) are well known for their anti-inflammatory properties. However, the effects of n-3 on cancer cachexia are still controversial. This systematic review and meta-analysis aim to evaluate the reported effects of n-3 supplementation on body weight and inflammatory markers in patients with cancer cachexia. Articles indexed in the major scientific platforms were retrieved in agreement with the Preferring Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) and 167 references were initially found. After removing duplicates and applying the inclusion and exclusion criteria, this systematic review included six studies. Using a random-effects model with 95 % confidence intervals (CI), three effect sizes were expressed as standard mean difference (SMD). No differences were found regarding the effect of n-3 on interleukin-6, C-reactive protein and albumin levels. Body weight analysis included only two studies, without robust conclusions. The low number of studies, low sample size and great intra-variability precludes a stronger analysis. More studies evaluating n-3 supplementation in cancer cachexia are still needed.